2023
DOI: 10.1186/s12934-023-02148-5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering transcriptional regulation of pentose metabolism in Rhodosporidium toruloides for improved conversion of xylose to bioproducts

Abstract: Efficient conversion of pentose sugars remains a significant barrier to the replacement of petroleum-derived chemicals with plant biomass-derived bioproducts. While the oleaginous yeast Rhodosporidiumtoruloides (also known as Rhodotorulatoruloides) has a relatively robust native metabolism of pentose sugars compared to other wild yeasts, faster assimilation of those sugars will be required for industrial utilization of pentoses. To increase the rate of pentose assimilation in R.toruloides, we leveraged previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…On the contrary, oleaginous R. toruloides can naturally assimilate pentose sugars, which is a great advantage in serving as a platform for converting low-value lignocellulose feedstock to high-value unusual fatty acid via metabolic engineering. Moreover, previous studies indicated that R. toruloides ’ ability to convert lignocellulosic feedstock into bioproducts could be improved through the enhancement of xylose assimilation and the adaptive evolution of the engineered strain (Coradetti et al, 2023; Díaz et al, 2018; Z. Liu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, oleaginous R. toruloides can naturally assimilate pentose sugars, which is a great advantage in serving as a platform for converting low-value lignocellulose feedstock to high-value unusual fatty acid via metabolic engineering. Moreover, previous studies indicated that R. toruloides ’ ability to convert lignocellulosic feedstock into bioproducts could be improved through the enhancement of xylose assimilation and the adaptive evolution of the engineered strain (Coradetti et al, 2023; Díaz et al, 2018; Z. Liu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…R. toruloides has an unusual xylose metabolism featuring the reduction to Darabitol, oxidation to D-ribulose, and phosphorylation to ribulose 5-phosphate (Adamczyk et (which , 2023). By overexpressing a putative transcription factor (RTO4_12978, Pnt1) that acts as a major regulator of pentose metabolism, the expression of enzymes involved in xylose catabolism was increased and the specific growth rate was improved significantly in cultures on xylose (Coradetti et al, 2023). Furthermore, the adaptation of R. toruloides through evolutionary strategies has also led to the development of strains with increased tolerance to the major inhibitors present in lignocellulosic hydrolysates (Díaz et al, 2018;Z.…”
Section: Converting Wood Hydrolysate Into Punicic Acid-containing Sin...mentioning
confidence: 99%
See 1 more Smart Citation